Visual cognition during real social interaction - Skarratt, Paul A. (Frontiers in Human Neuroscience, 2012)
Laboratory studies of social visual cognition often simulate the critical aspects of joint attention by having participants interact with a computer-generated avatar. Recently, there has been a movement toward examining these processes during authentic social interaction. In this review, we will focus on attention to faces, attentional misdirection, and a phenomenon we have termed social inhibition of return, that have revealed aspects of social cognition that were hitherto unknown. We attribute these discoveries to the use of paradigms that allow for more realistic social interactions to take place. We also point to an area that has begun to attract a considerable amount of interest – that of Theory of Mind and automatic perspective taking – and suggest that this too might benefit from adopting a similar approach.